Effect of Different Botanical Extracts and Organic Compound in The Management of Leaf Spot Disease of Strawberry (Fragaria ananassa Duch.) Caused by Pestalotia longisetula under Field Condition - Karki, Beautina; Sitaula, Hom Prasad; Bhandari, Sandesh; Gairhe, Pramod; Manandhar, Hira Kaji (International Journal of Applied Sciences and Biotechnology, 2021)
A field experiment was carried out using sweet sensation variety of strawberry to check the efficacy of different botanical extracts and organic compounds to manage leaf spot disease. The study was done using ten treatments viz; ginger (T1), turmeric (T2), garlic (T3), ginger + turmeric + garlic (T4), cow urine (T5), cow urine+ ginger + turmeric + garlic (T6), compost tea (T7), compost tea+ ginger+ turmeric+ garlic (T8), SAAF (mancozeb 63 % + carbendazim 12%) (T9) and control (T10), which was replicated thrice. The parameter observed during experiment were plant height, leaf number, disease leaves, stem lesions, yield, percent disease incidence, disease severity percent and percent disease control. At 75 days of transplantation, the highest plant height, leaf number (24.60) and yield (1391.67 gm/plot) were observed in treatment compost tea (18.14 cm), cow urine+ ginger+ turmeric+ garlic and garlic respectively and lowest in treatment control (16.19 cm, 23.27 & 566.67 gm/plot). The disease leaves and stem lesions were observed highest in treatment control (3.40&3.23) and lowest in treatments garlic (3.0), and cow urine+ ginger+ turmeric+ garlic (1.83) respectively at 75 days after transplantation. Moreover, the highest percent disease incidence and disease severity percent were observed highest in treatments control (28.94% & 84.81%) and percent disease control in treatment garlic (42.36%) at 75 days of transplantation. Therefore, it is suggested to use garlic extracts as a measure to control leaf spot disease of strawberry. Int. J. Appl. Sci. Biotechnol. Vol 9(3): 193-202.